One Country, Two Polarised Audiences: Estonia and the Deficiency of the Audiovisual Media Services Directive - Jõesaar, Andres (2015)
This article argues that until recent times, the Estonian media policy has mainly been interpreted as an economic issue and it did not account for the strategic need to build a comprehensive media field to serve all groups in society. This has happened despite the fact the Estonian media policy is in line with the European Union (EU) media policy, which should ensure freedom of information, diversity of opinion and media pluralism. Findings of the Estonian case study show that despite these noble aims, Estonia has two radically different information fields: one for Estonian speaking audiences and one for Russian speakers. Events in Ukraine have added to the democratic media policy paradigm a question of national security. Now it is a challenge for the policy makers to unite polarised media fields and how to minimise the impact of Russian propaganda. On the EU level, one supportive measure could be a revision of the Audiovisual Media Service Directive.